5, 6‐ and 6, 6‐Membered Palladium(II) Pincer Complexes Based on Functionalized Carboxamides with Ancillary Sulfur and Nitrogen Donors. Issue 33 (26th October 2016) - Churusova, Svetlana G.; Aleksanyan, Diana V.; Vasil'ev, Andrei A.; Nelyubina, Yulia V.; Novikov, Valentin V.; Pavlov, Alexander A.; Denisov, Gleb L.; Klemenkova, Zinaida S.; Kozlov, Vladimir A.
Abstract : New multidentate ligands have been synthesized by the condensation of 2‐(methylsulfanyl)benzoyl chloride with a range of amines bearing ancillary N or S donors. In reactions with PdCl2 (NCPh)2, the ligands smoothly underwent direct cyclopalladation to give pincer complexes with 5, 6‐ or 6, 6‐membered fused metallocycles. The oxidation of the sulfide ligands with H2 O2 afforded the corresponding sulfoxide derivatives, which readily formed analogous pincer complexes with the Pd II ions. The realization of κ 3 ‐ S, N, X coordination (X = N or S) was confirmed by multinuclear NMR and IR spectroscopic data and, in some cases, X‐ray crystallography. An unusual dynamic behavior of the 6, 6‐membered S, N, S complex with an organophosphorus ligand was additionally studied by the ROESY technique. All of the palladocycles obtained were tested as precatalysts for the Suzuki cross‐coupling of aryl bromides with arylboronic acids, which allowed us to evaluate the main structure–activity relationships. Abstract : Multidentate ligands based on functionalized carboxamides with ancillary N or S donors readily undergo direct cyclopalladation to afford Pd II pincer complexes with 5, 6‐ or 6, 6‐membered fused metallocycles. The preliminary evaluation of the catalytic activities of the resulting palladocycles in the Suzuki cross‐coupling allows the determination of the main structure–activity relationships.